Tinjauan Hukum Pidana Islam terhadap Pelaksanaan Kepres No. 174/Tahun 1999 Tentang Remisi dalam Kasus Pembunuhan - Muhammad Hariri (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2016)
This paper aims to find out how the legal review of remissions in murder cases, as stipulated in Presidential Decree No. 174 of 1999. Furthermore, it was concluded by the authors that: first, the crime of murder that gets remission has their respective criteria, in the sense of granting remission depending on where the sentence is, the sentence is classified as temporary or classified as a death sentence if the crime is temporary, then will get remission on condition - Certain conditions, if criminal with capital punishment, then it cannot be unless there are other provisions. Second, the procedures for implementing the remission of murder perpetrators must fulfill several conditions determined by the Presidential Decree and the Minister of Law. And third, if viewed from the Islamic criminal law the implementation of granting remissions for the perpetrators of murder is very good, because with the remission it can make someone to change their behavior and also provide an opportunity for the murderer to avoid the act again, with the aim and encouragement to back to the midst of society.